Alerting Doctors About Patient Life Challenges: A Randomized Control Trial of a Previsit Inventory of Contextual Factors. Issue 1 (May 2019) - Weaver, Frances M.; Binns-Calvey, Amy; Gonzalez, Beverly; Kostovich, Carol; LaVela, Sherri; Stroupe, Kevin T.; Kelly, Brendan; Ashley, Naomi; Miskevics, Scott; Gerber, Ben; Burkhart, Lisa; Schwartz, Alan; et al.
Objective. Effective care attends to relevant patient life context. We tested whether a patient-completed inventory helps providers contextualize care and increases patients' perception of patient-centered care (PCC).Method. The inventory listed six red flags (e.g., emergency room visits) and if the patient checked any, prompted for related contextual factors (e.g., transportation difficulties). Patients were randomized to complete the inventory or watch health videos prior to their visit. Patients presented their inventory results to providers during audio-recorded encounters. Audios were coded for physician probing and incorporating context in care plans. Patients completed the Consultation and Relational Empathy (CARE) instrument after the encounter.Results. A total of 272 Veterans were randomized. Adjusting for covariates and clustering within providers, inventory patients rated visits as more patient-centered (44.5; standard error = 1.1) than controls (42.7, standard error = 1.1, P = 0.04, CARE range = 10–50). Providers were more likely to probe red flags (odds ratio = 1.54; confidence interval = 1.07–2.22; P = 0.02) when receiving the inventory, but not incorporating context into care planning.Conclusion. A previsit inventory of life context increased perceptions of PCC and providers' likelihood of exploring context but not contextualizing care. Information about patients' life challenges is not sufficient to assure that context informs provider decision making even when provided at the point of care by patients themselves.